2019
DOI: 10.1021/acs.orglett.9b02921
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalyst-Free Visible-Light-Promoted C(sp2)–S Coupling: A Strategy for the Preparation of S-Aryl Dithiocarbamates

Abstract: We have successfully developed a green and efficient multicomponent reaction protocol to synthesize S-aryl dithiocarbamates under visible light. Most appealingly, the reaction can proceed smoothly without adding any transition-metal catalysts, ligands, or photocatalysts while minimizing chemical wastes and metal residues in the end products. The advantages of this method meet the requirements of sustainable and green synthetic chemistry, and it provides a straightforward way to create valuable S-aryl dithiocar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
49
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 125 publications
(53 citation statements)
references
References 71 publications
0
49
0
Order By: Relevance
“…Electron paramagnetic resonance (EPR) spectroscopy further supported the reduction of alkenes to generate alkyl radicals in this system (Figures 3f and 3g). The experiments using 13 C-labeled CO 2 generated the 2a, sodium formate, and sodium oxalate, all with 13 C-labeling (Figure 3h). Moreover, both sodium formate and sodium oxalate were detected under the reaction conditions in the absence of alkenes (Figure 3i), which suggested that CO 2 could be also reduced in such highly reductive conditions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Electron paramagnetic resonance (EPR) spectroscopy further supported the reduction of alkenes to generate alkyl radicals in this system (Figures 3f and 3g). The experiments using 13 C-labeled CO 2 generated the 2a, sodium formate, and sodium oxalate, all with 13 C-labeling (Figure 3h). Moreover, both sodium formate and sodium oxalate were detected under the reaction conditions in the absence of alkenes (Figure 3i), which suggested that CO 2 could be also reduced in such highly reductive conditions.…”
Section: Resultsmentioning
confidence: 99%
“…[7][8][9] For example, Wang reported a novel visible-light-driven CTC of alkenes and disulfides with alkenes as electron donors and disulfides as electron acceptors (Figure 1b). 9 While few examples of CTCs of thiolates and (hetero)arenes have been reported, [10][11][12][13] to the best of our knowledge, the CTCs of thiolates and acrylates/styrenes have not been reported.…”
Section: Introductionmentioning
confidence: 99%
“…[5] Moreover, high-cost noble metals, complicated synthetic preparations, air-free reaction conditions, and sometimes moderate activity also restricted their practical applications. [6] Therefore, the development of easy-toproduce heterogeneous photocatalysts with the ability of easy catalyst separation and recyclability is currently highly required and thus of great significance. [7] Compared to the exploration of homogeneous photocatalysts in photocatalytic organic transformations, heterogeneous photocatalysts are much less explored.…”
mentioning
confidence: 99%
“…In the past decade, visible‐light promoted organic synthesis has emerged as a highly economical and eco‐friendly strategy for the construction of various chemical bonds under mild conditions . Particularly, visible‐light photoredox catalysis is an ideal tool to initiate radical cascade reactions for the synthesis of heterocycles .…”
Section: Radical Strategies For the Synthesis Of 3‐substituted Chrmentioning
confidence: 99%